LncRNA NKILA suppresses colon cancer cell proliferation and migration by inactivating PI3K/Akt pathway - Huang, Jian; Zhao, Lingfeng; Chen, Wei; Duan, Jian; Shrestha, Dibesh; Zhou, Ruize; Tuo, Xiaoyu; Zhu, Zhu (Translational Cancer Research; Vol 7, No 6 (December 30, 2018): Translational Cancer Research, 2018)
Background: LncRNA NKILA has been reported to play a role as tumor suppressor in the development of various human cancers. However, functionality of NKILA in the development of colon cancer still hasn’t been reported. Methods: In this study, expression of NKILA in tumor tissues of patients with different stages of colon cancer was detected by qRT-PCR. Effects of NKILA knockdown and overexpression on migration and invasion of different colorectal adenocarcinoma cell lines were investigated by Transwell invasion and migration assay, respectively. Interaction between NKILA and PI3K/Akt pathway was explored by western blot. Results: We found that expression level of NKILA was reduced with the development of colon cancer. NKILA knockdown promoted the migration and invasion of different colorectal adenocarcinoma cell lines, induced the activation of PI3K/Akt pathway and promoted tumor growth in mice, while NKILA overexpression played an opposite role. Conclusions: We conclude that NKILA can suppress proliferation and migration of colon cancer cell by inhibiting the activation of PI3K/Akt pathway.